2007
DOI: 10.1111/j.1095-8649.2007.01525.x
|View full text |Cite
|
Sign up to set email alerts
|

Annual cycle of stored spermatozoa within the ovaries of Helicolenus dactylopterus dactylopterus (Teleostei, Scorpaenidae)

Abstract: The aim of this work was to analyse the ultrastructure of storage crypts and stored spermatozoa, and to describe changes during the annual reproductive cycle of the bluemouth Helicolenus dactylopterus dactylopterus, which has internal fertilization and a zygoparous mode of reproduction. Spermatozoa had elongated heads and long midpieces, two characteristics which are thought to be fairly advanced and correlated with internal fertilization, as is the case of the bluemouth. A remarkable spermatozoon feature was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…However, all cells remained discrete as evidenced by the lack of membrane fusion. More complex relationships are described in nonauchenipterid fishes (Vila et al, 2007).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…However, all cells remained discrete as evidenced by the lack of membrane fusion. More complex relationships are described in nonauchenipterid fishes (Vila et al, 2007).…”
Section: Discussionmentioning
confidence: 98%
“…Being functionally active, as indicated by a number of morphological characteristics (i.e., pronounced nuclear indentation, nucleoli and smooth endoplasmic reticulum), the epithelial cells in this study may participate in the nourishment of the inseminated spermatozoon. Adjacent lamellar epithelial cells are joined together by junctional complexes (this study) the function of which has been regarded as forming a barrier to protect the spermatozoa from the female immune system (Koya et al, 1997;Vila et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…As for its reproductive biology, a previous study has shown that it is an ovo‐zygoparous species (Muñoz et al , 2002 a ), which implies a level of oviparity specialization. Fertilization is internal, and the female is able to store sperm in the ovary for long periods of time, within specialized interlamellar structures (Muñoz et al , 1999, 2000) where male sex cells are maintained in a viable state and protected from the female immune system (Muñoz et al , 2002 b ; Vila et al , 2007) until oocytes mature. Sperm is then released towards the ovarian lumen to fertilize the mature oocytes.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of empty cysts inside the ovaries during the spawning and post‐spawning periods is indicative of recent fertilization, as suggested by Vila et al . ().…”
Section: Discussionmentioning
confidence: 99%